Nostalgia a muzyka - Dyrlica, Małgorzata (Studia Rossica Posnaniensia, 2019)
This article is an attempt to answer the question of what nostalgia is in music. The author makes a distinction between the emotions of the author, the performer and the recipient as well as the emotional qualities of the work itself. She also tries to describe the means of artistic expression that foster the impression of nostalgia in music.